2021
DOI: 10.1126/sciadv.abe3954
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Abi3 gene locus exacerbates neuropathological features of Alzheimer’s disease in a mouse model of Aβ amyloidosis

Abstract: A cytoskeleton-associated protein regulates microglial function and affects Alzheimer’s disease phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 83 publications
(114 reference statements)
6
31
0
Order By: Relevance
“…Mouse brain slices (350µm) containing the dorsal striatum were made from 7-10 week-old male and female mice using a Leica VT1200S vibratome, as previously described [75]. Slices recovered in artificial cerebral spinal fluid (aCSF) solution (30°C) for 1-hour then transferred to room temperature until field excitatory postsynaptic currents (fEPSPs) were recorded as described in [76] and supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Mouse brain slices (350µm) containing the dorsal striatum were made from 7-10 week-old male and female mice using a Leica VT1200S vibratome, as previously described [75]. Slices recovered in artificial cerebral spinal fluid (aCSF) solution (30°C) for 1-hour then transferred to room temperature until field excitatory postsynaptic currents (fEPSPs) were recorded as described in [76] and supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Another novel non-synonymous variant ABI3 (rs616338, p.Ser209Phe), increased the risk for the development of late-onset AD ( Sims et al, 2017a ; Conway et al, 2018 ; Olive et al, 2020 ). The ABI3 immunoreactivity was barely detectable in the brains of cognitively normal human; however, ABI3 was preferentially expressed in activated microglia in close proximity to Aβ plaques in AD patients ( Satoh et al, 2017 ; Karahan et al, 2021 ). Genetic deletion of ABI3 exacerbated Aβ deposition in 5xFAD mice.…”
Section: Microglia-related Risk Factors For Late-onset Alzheimer’s Di...mentioning
confidence: 98%
“…Since ABI3 is known to regulate actin cytoskeleton organization ( Sekino et al, 2015 ), an important process for microglial migration, deletion of ABI3 might prevent the clustering of active microglia around Aβ plaques and thereby impairing effective Aβ clearance in AD mice ( Karahan et al, 2021 ). More importantly, cultured microglia with ABI3 deletion displayed defective microglial phagocytosis which might also accounted for the increased Aβ deposition in 5xFAD mice ( Karahan et al, 2021 ). It is known that severe niacin deficiency is a cause of dementia, and dietary intake of niacin protected individuals from the development of AD ( Morris et al, 2004 ).…”
Section: Microglia-related Risk Factors For Late-onset Alzheimer’s Di...mentioning
confidence: 99%
“…Thus far, the genes and loci implicated in LOAD genetic risk have nominated multiple pathways for disease relevance, including endosomal trafficking, cholesterol regulation, mitochondrial function, and inflammation and immunity 13 , most of which are active in multiple cell types in the brain. Due to the discovery of LOAD-associated coding variation in genes such as TREM2 1416 , PLCG2 14,17 , and ABI3 14 , which are predominantly expressed in microglia, functional studies in both cell and animal models have increasingly been focused on the role of microglial biology with regard to genetic risk for LOAD and the pathways listed above 1822 . However, in contrast to previous work which had highlighted the importance of microglia-expressed genes to transcriptional network dysregulation in the LOAD brain 23 , a recent co-expression network study of brain RNA-seq data from a large-scale LOAD cohort found neuron-specific co-expression modules to be the most profoundly affected by disease state 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the genes and loci implicated in LOAD genetic risk have nominated multiple pathways for disease relevance, including endosomal trafficking, cholesterol regulation, mitochondrial function, and inflammation and immunity 13 , most of which are active in multiple cell types in the brain. Due to the discovery of LOAD-associated coding variation in genes such as TREM2 [14][15][16] , PLCG2 14,17 , and ABI3 14 , which are predominantly expressed in microglia, functional studies in both cell and animal models have increasingly been focused on the role of microglial biology with regard to genetic risk for LOAD and the pathways listed above [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%